Les charges d’enseignement dans les universités québécoises : une réplique au Rapport Gobeil - Belanger, Charles H.; LaCroix, Robert; Raynauld, Andre (Canadian Journal of Higher Education, 1987)
This article responds to the recommendation in the "Gobeil Report" (Rapport Gobeil) which proposes an increase in teaching workload of 50% in all Quebec universities in order to conform to what "exists" elsewhere in Canada. After having undertaken a survey among 39 Canadian universities of all sizes, and after having analysed the number of students at the graduate and/or undergraduate levels as well as the amount of grant assistance provided to research, the authors conclude that it is necessary to distinguish between two types of university establishments: research universities and teaching universities. Results demonstrate clearly that course hours represent but one component of the teaching load and that it is also necessary to consider the graduate studies program of the institution as well as the research activities being undertaken by the university before drawing a conclusion as general as that presented in the Gobeil Report. The authors of this study conclude that there is a net difference in the teaching responsibilities in Canadian universities outside of Quebec — whether it be a research or a teaching university. In the francophone universities of Quebec, teaching loads are uniform no matter what the commitment to research or advanced studies happens to be. An indiscriminate increase in the teaching assignment would compromise graduate studies and the research carried out in research universities.